Metamorphosis in Drosophila and other insects: the fate of neurons throughout the stages. - Tissot, M.; Stocker, R.F. (Progress in neurobiology, 2000)
The nervous system of insects is profoundly reorganised during metamorphosis, affecting the fate of different types of neuron in different ways. Almost all adult motor neurons derive from larval motor neurons that are respecified for adult functions. A subset of larval motor neurons, those which mediate larval- or ecdysis-specific behaviours, die before and immediately after eclosion, respectively. Many adult interneurons develop from larval interneurons, whereas those related to complex adult sense organs originate during larval life from persisting embryonic neuroblasts. Sensory neurons of larvae and adults derive from essentially two distinct sources. Larval sensory neurons are formed in the embryonic integument and - with few exceptions - die during metamorphosis. Their adult counterparts, on the other hand, arise from imaginal discs. Special emphasis is given in this review to the metamorphic remodelling of persisting neurons, both at the input and output levels, and to the associated behavioural changes. Other sections deal with the programmed death of motor neurons and its causes, as well as with the metamorphic interactions between motor neurons and their target muscles. Remodelling and apoptosis of these two elements appear to be under independent ecdysteroid control. This review focusses on the two most thoroughly studied holometabolous species, the fruitfly Drosophila melanogaster and the tobacco hornworm moth Manduca sexta. While Manduca has a long tradition in neurodevelopmental studies due to the identification of many of its neurons, Drosophila has been increasingly used to investigate neural reorganisation thanks to neurogenetic tools and molecular approaches. The wealth of information available emphasises the strength of the insect model system used in developmental studies, rendering it clearly the most important system for studies at the cellular level.